Cattle Grazing Effects on Vegetation and Wild Ungulates in the Forest Ecosystem of a National Park in Northeastern China - Roberts, Nathan James; Zhang, Yueheng; Convery, Ian; Liang, Xin; Smith, Darrell; Jiang, Guangshun (Frontiers in Ecology and Evolution, 2021)
There is evidence that cattle grazing in forests limits big cat abundance. There is concern, too, about competition with wild ungulate prey through bottom-up effects on vegetation. Hence, there have been calls to remove or control forest livestock grazing in aid of restoring endangered large carnivores and their prey. To help inform scientific debate and decision making, we explored cattle-vegetation-prey dynamics in Northeast Tiger and Leopard National Park, northeast China and present a reappraisal of livestock grazing in the context of coexistence and an integrated approach to land use in China. Inside long-term forest grazing enclosures, wild boar (Sus scrofa) density increased with cattle density. Roe deer (Capreolus pygargus) density and occurrence probability of wild boar and roe deer were not influenced by cattle density. Wild ungulate densities were not related with the number of annual shoots, i.e., forage plant abundance. The presence/absence and abundance of annual shoots was not related with cattle density. Wild ungulate density had mixed associations with vegetation structure; arbor tree diameter at breast height (DBH) and habitat ‘openness’ increased with cattle density. Finally, inside and outside enclosures had different vegetation characteristics and wild boar densities, while roe deer densities were equal. We conclude that cattle density and associated changes to vegetation have positive, negative, and neutral effects on two wild ungulate prey species. Each of these factors warrant consideration in evidence-based management decisions in regard to regulating ungulate community composition to support different large predators as preferred prey in core areas and corridors of habitats.